The Impact of Creative Writing Activity on EFL Learners' Non-Core Vocabulary Acquisition - Antonio Moreno Jurado (Journal of English Language Teaching and Linguistics, 2023)
In the context of ELT and EFL classrooms, creative writing has been underutilized in language learning and critical consciousness development (Stillar, 2013). This paper presents a quantitative approach that aims to explore the impact of a creative writing activity in terms of non-core vocabulary acquisition within B2-level EFL classrooms. By conveying a set of in-class and autonomous creative writing activities, the study deepens not only into vocabulary acquisition but also into second language acquisition (SLA) purposes. The investigation aims to discover the extent to which the instruction of creative writing activities fosters EFL learners’ acquisition of non-nuclear vocabulary. Following a quantitative methodology, a non-core vocabulary pre-test and post-test were administered to students. These tests included sections for analyzing students' knowledge of non-core vocabulary and the linguistic repertoire used in vignette descriptions (strip comics). Results from a paired samples t-test suggested that integrating creative writing activities in EFL environments not only enhanced lexical acquisition but also fostered detachment from cultural nuances and the influence of the students' mother tongue. All the scrutinized elements within the students’ linguistic repertoire were improved after the creative writing instruction. Within this analysis, the verbs and adjectives were the elements that were the most improved in terms of specificity and concreteness. Overall, the study sheds light on the potential benefits of integrating creative writing activities in EFL classrooms. The findings hold promising implications for EFL educators seeking innovative strategies to enhance language learning and intercultural competence.